STRUKTUR PERUSAHAAN DAN PROFITABILITAS PADA INDUSTRI REAL ESTATE DAN PROPERTY DI INDONESIA - Fadjar O.P. Siahaan (University of Merdeka Malang, 2013)
Real estate property industry was a sector which had difficult characteristics to predict and high risk. WhenEconomy growth was high, it was booming and tended to be over supplied and the main capital was generallygot through bank loans. The purpose of this research was to analyze the impact of firm structure consisting ofthe firm size, firm age, capital structure, and stock ownership toward profitability measured using ROI andROE. The sample was selected using purposive sampling with 120 observations from 52 real estate propertycompanies listed in Indonesian Stock Exchange in 2009 2011. By using multiple regression, the result of thisresearch showed that firm size had positive significant effect on ROI and ROE; firm age had negative significanteffect on ROI but it did not have significant effect on ROE; capital structure had positive significant effecton ROE but did not have significant effect on ROI; public ownership had negative significant effect on ROIand ROE.